Analysis of Physics Concepts in Playgrounds at GoFun Bojonegoro as Learning Materials for Students - Mustafarah, Vinka Amalia; Christi Alfiah, Lina; Dwikoranto, Dwikoranto; Ainur Rizki, Iqbal (JPPS (Jurnal Penelitian Pendidikan Sains), 2024)
Objective: GoFun Bojonegoro is one of the area edutainments in Bojonegoro which has rides for games and entertainment with an attractive appeal for visitors. This study aims to analyse the physics concepts that exist in several game rides in GoFun Bojonegoro Theme Park. Some of the rides available at the park have interesting physics concepts to learn. Method: This type of research is descriptive qualitative research with observation, documentation, and analysis methods as a form of data collection. Results: There are three vehicles analysed namely, Pirates Ship, Mini Ontang-Anting, and Bom-Bom Car, which works based on the concept of physics. There are various physics concepts in the vehicle, such as the concept of oscillation, centrifugal force, circular motion, Newton's third law, collision, and the law of conservation of momentum and impulse. By integrating physics learning in the vehicle or edutainment make learning more fun. Novelty: This research provides edutainment-based learning that can increase the effectiveness of students in learning physics concepts and make students more active and learning looks fun.